Hematopoietic stem cell transplantation in T-prolymphocytic leukemia: a retrospective study from the European Group for Blood and Marrow Transplantation and the Royal Marsden Consortium - Jędrzejczak, Wiesław; Dreger, Peter (Leukemia, 2012)
T-prolymphocytic leukemia (T-PLL) has a very poor prognosis with conventional immunochemotherapy. Incidental reports suggest that allogeneic hematopoietic stem cell transplantation (allo-HSCT) might have a role in this disease. Therefore, the purpose of the present study was to analyze the outcome of transplants for T-PLL registered with the European Group for Blood and Marrow Transplantation database and the Royal Marsden Consortium. Eligible were 41 patients with a median age of 51 (24-71) years; median time from diagnosis to treatment was 12 months, and in complete remission (CR) (11), partial remission (PR) (12), stable or progressive disease (13) and unknown in 5 patients. A total of 13 patients (31%) received reduced-intensity conditioning. Donors were HLA-identical siblings in 21 patients, matched unrelated donors in 20 patients. With a median follow-up of surviving patients of 36 months, 3-year relapse-free survival (RFS) and OS was 19% (95% CI, 6-31%) and 21% (95% CI, 7-34%), respectively. Multivariate analysis identified TBI and a short interval between diagnosis and HSCT as factors associated with favorable RFS. Three-year non relapse mortality and relapse incidence were each 41% with the majority of relapses occurring within the first year. These data indicate that allo-HSCT may provide effective disease control in selected patients with T-PLL.